The postdoc landscape : the invisible scholars - Jaeger, Auy J.; Dinin, Alessan J. (Academic Press, an imprint of Elsevier, 2018)
The Postdoc Landscape offers historical, international, and domestic examples, solutions, and strategies for addressing the needs of postdoctoral scholars in terms of their presence in government, industry, and the academy. Growing issues and concerns are identified with a clear direction in terms of what practitioners, policymakers, and educators can do to improve the working conditions of postdoctoral scholars. The book includes chapters centered on three themes: the Postdoc Landscape, Postdoc Support and Postdoc Career Literacy, Agency and Choice. This comprehensive reference serves as a guide for scholars, individuals who supervise and mentor postdoctoral scholars and policymakers.